1993
DOI: 10.1111/j.1365-2133.1993.tb11841.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight, keratotic skin lesions and skin cancer in renal transplant recipients

Abstract: In a retrospective follow-up study, 36 renal transplant recipients with, and 101 without, skin cancer, who had received their first transplant before January 1981 and who were still alive with a functioning graft on 1 August 1989, were assessed to determine the risk of non-melanoma skin cancer in relation to exposure to sunlight during childhood and adolescence. The contribution of the number of keratotic skin lesions to the skin cancer risk was also assessed. The estimated relative risks (odds ratios) of skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
8

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(86 citation statements)
references
References 23 publications
2
76
0
8
Order By: Relevance
“…The incidence of BCC is much more common in individuals who have received a solid organ transplant 90,91 in whom herpes virus like DNA sequences have been demonstrated 90,91 and in whom tumors appear to have an increased tendency for recurrence and metastasis. 92 In concert with this more aggressive behavior, the histologic types are different in patients with immune suppression in whom infiltrative growth BCC is more common than nodular and/or superficial variants.…”
Section: Uv Light-induced Mutagenesis and Biologic Transformationmentioning
confidence: 99%
“…The incidence of BCC is much more common in individuals who have received a solid organ transplant 90,91 in whom herpes virus like DNA sequences have been demonstrated 90,91 and in whom tumors appear to have an increased tendency for recurrence and metastasis. 92 In concert with this more aggressive behavior, the histologic types are different in patients with immune suppression in whom infiltrative growth BCC is more common than nodular and/or superficial variants.…”
Section: Uv Light-induced Mutagenesis and Biologic Transformationmentioning
confidence: 99%
“…Risk factors for skin cancer in both transplant and nontransplant patients are similar (Bouwes Bavinck et al, 1993) and cutaneous, mucosal and EV-related HPV sequences are found in a high porportion of both BCC and SCC in both patient groups (McGregor and Proby, 1996). We have examined the spectrum of p53 mutations in post-transplant compared with sporadic skin cancers, and show that p53 mutations, predominantly of a u.v.-related nature, are present irrespective of HPV status.…”
mentioning
confidence: 93%
“…Renal transplant patients, who are therapeutically immunosuppressed, display exceptionally high incidence of squamous cell carcinoma and basal cell carcinoma on sun-exposed sites. 39,40 In the general population, certain individuals seem to be more susceptible than others to the immunosuppressive effects of solar radiation. 41 Following exposure of the skin to ultraviolet radiation, 40% of normal subjects exhibit suppressed contact hypersensitivity responses to the topically applied experimental sensitizer, dinitrochlorobenzene, at the site of exposure.…”
Section: Ultraviolet-b-induced Immunosuppression In Photocarcinogenesismentioning
confidence: 99%